Integrated multi-omics analyses combined with western blotting discovered that cis-TSG alleviated liver injury via modulating lipid metabolism - Teka, Tekleab; Wu, Jiang; Oduro, Patrick Kwabena; Li, Ze; Wang, Chenxi; Chen, Hao; Zhang, Lin; Wang, Haitao; Wang, Liming; Han, Lifeng (Frontiers in Pharmacology, 2024)
Polygonum multiflorum shows dual hepatoprotective and hepatotoxic effects, necessitating detailed investigations into its bioactive components, particularly the stilbene glycosides, responsible for this duality effect. This study examined the pharmacological effects of cis-TSG, a stilbene glycoside, on ANIT-induced cholestasis in C57BL/6J mice. ANIT administration led to significant liver injury, as indicated by elevated ALT and AST levels and disrupted lipid metabolism. cis-TSG treatment significantly reduced ALT and AST levels, restored normal lipid profiles, and mitigated histological liver damage. Metabolomic and lipidomic analyses revealed that cis-TSG modulated key metabolic pathways, including glycerophospholipid metabolism, sphingolipid metabolism, and bile acid biosynthesis.Notably, cis-TSG increased levels of MUFAs and PUFAs, enhancing PPARα activation, which contributed to its hepatoprotective effects. Transcriptomic analysis supported these findings, showing downregulation of genes involved in lipid metabolism, inflammation, and oxidative stress in the cis-TSG-treated group. These results suggest that cis-TSG mitigates ANIT-induced cholestasis through the modulation of lipid metabolism and activation of PPARα. Our findings provide new insights into the therapeutic potential of cis-TSG for liver diseases and underscore the need for further research to fully elucidate its mechanisms of action.